EPISTEMOLOGICAL POSTULATES OF AFRICAN INDEGINOUS EDUCATION INHERENT IN THE KENYAN EDUCATION SYSTEM - Shani, Ominde Eliud (IJRDO- Journal of Educational Research, 2017)
The paper examines the concept of knowledge in African indigenous education. Traditional African education has specific epistemological postulates that are relevant to the Kenyan education system. The study also explores some of the shortcomings of African indigenous education.